Continuity or replacement
1 online resource (352 pages).
Keywords: This volume is based on the symposium on controversies in 'Homo sapiens evolution' in Zagreb. It examines the competing models for modern human origins within the framework of present-day knowledge in the areas of human paleontology, paleolithic archaeology, and molecular genetics.